KUALITAS PELAYANAN PT POS INDONESIA CABANG BARITO SELATAN - Resmiati Sari; Dra. Puput Ratnasari, M.Hum; Katriani Puspita Ayu, SE., MA (Universitas Palangka Raya, 2020)
This study was conducted to determine how the quality of service at PT Pos Indonesia branch of South Barito and what efforts are conducted by PT Pos Indonesia branch of South Barito to improve the quality of service to the community . Based on these problems ,the purpose of the study was to describe and analyze the quality of service at PT Pos Indonesia branch of South Barito and the efforts of PT Pos Indonesia to maximize service to the community. The focus of research on the quality of financial services is measured based on five dimensions of service quality that is reability, responsiveness, assurance, empathy, tangibles and the efforts undertaken by PT Pos Indonesia South Barito branch in maximizing service to the community. This type of research is qualitative research and data collection techniques performed by the method of observation , interviews , and documentation. Subjects of this study were employees of PT Pos Indonesia branch of South Barito and public users of financial services branch of PT Pos Indonesia South Barito . Mechanical analysis of data from this study is data collection , data reduction , data presentation , and conclusion and verification Conclusions drawn or obtained from this study indicate that the quality of service of PT Pos Indonesia Branch South Barito still not up to optimum . It can be inferred from the existence of public complaints as users of services provided related services and facilities are incomplete and inadequate .